Treatment of open fracture of shaft of tibia-fibula Gustilo type III-B by SIGN interlocking nail and wound coverage by muscle flap within 72 hours of injury - Ali, Ayub; Rahman, Mizanur; Faruquee, Sajedur Reza; Islam, Tazul; Rahim, Zamil Zaidur; Yusuf, Abdullah (International Journal of Research in Orthopaedics, 2017)
Background: The open fracture of tibia-fibula Gustilo type III-B may threaten the survival of the injured leg. The objective of the study purpose was to see the effect of early coverage following fixation of open tibial shaft fracture. Methods: This clinical trial was carried out in National Institute of Traumatology and Orthopaedic Rehabilitation (NITOR), Dhaka from July 2004 to June 2006 for a period of two (2) years. Patients at age group of 18 years or above with both sexes presented with open fracture shaft of tibia-fibula Gustilo type III-B were selected as study population. The patients were surgically managed by SIGN Interlocking nail and wound coverage by muscle flap within 72 hours of injury. Bacteriological study of the wound was done in all cases. All fixation and coverage were performed within 72 hours of injury. Patients grading improved on subsequent follow up. Evaluation of results was done at every post-operative follow up. Results: A total number of 12 young patients with open fracture tibia-fibula Gustilo III-B were recruited for this study. Their age varies from 18 years to 48 years. A total number of 83.33% cases wound debridement was done within 12 hours of injury. Most of the soft tissue healed (91.67%) within 0 to 20 days. There were no cases developed limb length discrepancy angulations or rotation. Superficial infections were occurred in 1(8.33%) case but no evidence of deep infection. In this study excellent result were obtained from 9 cases (75%), good results were found in 2 cases (16.67%), fair results from 1 case (8.33%). Conclusions: In conclusion early intramedullary fixation and exposed bone coverage by muscle flap is very important for prevention of infection, minimizing bone death simultaneously enhances bone healing.